Increasing Student Engagement Within the Core Nutritional Sciences Curriculum: A Gameful Learning Approach. (December 2019) - Bridges, Dave; Hisamatsu, Rina; Anderson, Olivia S.
Innovative learning strategies are constantly developed to increase student engagement and application of course content to improve learning outcomes. Gameful Learning pedagogy is one such strategy that builds students' intrinsic motivation, confidence, and engagement to course material by allowing them to choose from a menu of optional assignments to earn points toward a grade. Little is known about student perceptions and outcomes from applying this pedagogy to dietetics and nutritional sciences graduate-level curricula. This article describes the implementation of Gameful Learning to an Accreditation Council for Education in Nutrition and Dietetics–accredited nutritional sciences graduate degree course and evaluates student perceptions and outcomes. Two student cohorts from 2016 (pre–Gameful Learning) and 2017 (implementation of Gameful Learning) who were enrolled in a nutritional sciences graduate-level course were compared. Student teaching evaluations were compared across cohorts. Specific items measuring student perceptions of fairness, knowledge gained, and workload were analyzed. Mann–Whitney nonparametric tests compared groups and Spearman's rank correlation coefficient measured associations. There was a positive correlation between total points and optional points (Pearson's r = 0.513, p = .0001). There was an overall increased perception toward the excellence of the course (3.82 to 4.13; 5-point Likert-type scale), improved sense of fairness (3.79 to 4.17; p = .036), and increased perception of workload (2.35 to 2.20; where 1 student indicated more work and 5 indicated less work). Although challenges in workload exist, Gameful Learning strategies aid in improving student outcomes and perceptions of course material by facilitating student autonomy and engagement with course content.